1997
DOI: 10.1159/000283057
|View full text |Cite
|
Sign up to set email alerts
|

Ureteroscopic Treatment of Ureteral Stones: Only an Auxiliary Measure of Extracorporeal Shockwave Lithotripsy or a Primary Therapeutic Option?

Abstract: Both extracorporeal Shockwave lithotripsy (ESWL) and ureteroscopy are well-established methods in stone treatment; however, the therapeutic procedure in ureteral calculi, especially in the distal third of the ureter, is still controversially discussed. The aim of the present study was to examine the role of ureteroscopy as an auxiliary measure after ESWL and its importance as an alternative therapeutic option in the treatment of distal ureteral stones. Between 1991 and 1994, 115 ureteroscopic procedures in 104… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 20 publications
(29 reference statements)
0
7
0
Order By: Relevance
“…ESWL has the obvious advantages of minimally invasive therapies, with no requirement for anaesthesia, treatment on an outpatient basis, a low morbidity rate [ 9, 10] and a high patient compliance (99% in the present study). If the patient accepts the re‐treatment rate and wishes to avoid a surgical procedure then ESWL would appear to be a reasonable first‐line treatment for stones in all locations within the ureter.…”
Section: Discussionmentioning
confidence: 70%
“…ESWL has the obvious advantages of minimally invasive therapies, with no requirement for anaesthesia, treatment on an outpatient basis, a low morbidity rate [ 9, 10] and a high patient compliance (99% in the present study). If the patient accepts the re‐treatment rate and wishes to avoid a surgical procedure then ESWL would appear to be a reasonable first‐line treatment for stones in all locations within the ureter.…”
Section: Discussionmentioning
confidence: 70%
“…All these changes may cause more impacted stones. Severs studies have shown the phenomenon that the impacted stone rates are signi cantly higher after unsuccessful SWL [19][20][21], which may cause di culty and even more complications during URS. In our study, we also found that impacted stones and ureteral in ammation edema were seen predominantly in patients having already undergone SWL.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, the success rates of URS with or without unsuccessful SWL were not statistically signi cant. The success rates of URS sessions after SWL failure ranged from 73.6%-78.9% [19][20][21]. In their researches, the stones were less than 10 mm in diameter.…”
Section: Discussionmentioning
confidence: 99%
“…Technical advancement in endoscope design and miniaturization have allowed surgeons to access calculi throughout the collecting system and regards as a gold standard for management of ureteral stones [1]. The stone free rates with the use of semi-rigid or flexible ureteroscopes have increased to 90% -100% for the distal ureteral calculi and to 74% for proximal ureteral calculi [2]. Moreover an impressive 95% of the patients were stone free rate after a single procedure [3].…”
Section: Introductionmentioning
confidence: 99%